Chapter Scuola, didattica e territorio: come rivitalizzare il rapporto con il contesto locale - Oliviero, Stefano (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper attempts to make an initial discussion on the usefulness of the history of education for interpreting the synergies between school, didactics and territory as they evolve over time. The paper offers a quick analysis of the pedagogical debate and political-organisational changes and then moves on to more practical and didactic issues. The paper also indicates some of the potentials of the approach offered by the history of education as applied history to revitalise the relationship with the local context.